The aryl hydrocarbon receptor pathway: a linking bridge between the gut microbiome and neurodegenerative diseases - Coretti, Lorena; Buommino, Elisabetta; Lembo, Francesca (Frontiers in Cellular Neuroscience, 2024)
The Aryl hydrocarbon receptor (AHR) is a cytosolic receptor and ligand-activated transcription factor widely expressed across various cell types in the body. Its signaling is vital for host responses at barrier sites, regulating epithelial renewal, barrier integrity, and the activities of several types of immune cells. This makes AHR essential for various cellular responses during aging, especially those governing inflammation and immunity. In this review, we provided an overview of the mechanisms by which the AHR mediates inflammatory response at gut and brain level through signals from intestinal microbes. The age-related reduction of gut microbiota functions is perceived as a trigger of aberrant immune responses linking gut and brain inflammation to neurodegeneration. Thus, we explored gut microbiome impact on the nature and availability of AHR ligands and outcomes for several signaling pathways involved in neurodegenerative diseases and age-associated decline of brain functions, with an insight on Parkinson's and Alzheimer's diseases, the most common neurodegenerative diseases in the elderly. Specifically, we focused on microbial tryptophan catabolism responsible for the production of several AHR ligands. Perspectives for the development of microbiota-based interventions targeting AHR activity are presented for a healthy aging.